Trends in Corporate Governance - HERMALIN, BENJAMIN E. (Journal of Finance, 2005)
ABSTRACT The popular press and scholarly studies have noted a number of trends in corporate governance. This article addresses, from a theoretical perspective, whether these trends are linked. And, if so, how? The article finds that a trend toward greater board diligence will lead, sometimes through subtle or indirect mechanisms, to trends toward more external candidates becoming CEO, shorter tenures for CEOs, more effort/less perquisite consumption by CEOs (even though such behavior is not directly monitored), and greater CEO compensation. An additional prediction is that, under plausible conditions, externally hired CEOs should have shorter tenures, on average, than internally hired CEOs.